การวิเคราะห์ค่าสุดโต่งแบบคู่ของราคาหลักทรัพย์กลุ่มขนส่งและโลจิสติกส์ ในตลาดหลักทรัพย์แห่งประเทศไทย - สุนิษา ตุ้ยยวง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The study aimed to test the conditions of bivariate extreme maximum returns of the transportation and logistics sector of the Stock Exchange of Thailand. Two selected securities including Airports of Thailand Public Company Limited (AOT) and BTS Group Holdings Public Company Limited (BTS) were experimented. Price datafor AOT and BTSsecuritiescollected directly from the transportation and logistics sector of the SET with thecloseof the day.Data used were 1,558 daily closing prices of securities during the period of January 2, 2008 to May 20, 2014. The estimations of Bivariate Generalized Extreme Value distribution (BGEV) and Bivariate Generalized Pareto Distribution (BGPD) were conducted. As the data were time-series, Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) unit root test were employed for testing stationary of collected daily data. The results showed that closing stock price and SET index were stationary at “I(0)”. Thus, AOT and BTS could be determined to test bivariate extreme value by utilizing the estimations of BGEV and BGPD. The performances of AOT and BTS have ranked the biggest market capitalizationsof transportation and logistics sector. The earning of two companies was a great extent. By testing BGEV and BGPD the results indicated that stock price of AOT is imperfect extremely relation form with SET and also that the stock price of BTS is imperfect extremely relation with SET.